Chemical and Microbiological Contamination in Ground Species from Traditional Markets in Yogyakarta - Kumalasari, Ika Dyah; Aryati, Erika Gaby (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2026)
Food safety is a critical component of food quality and requiries stringent measures to prevent biological, chemical, and other contaminants that pose risks to human health. This study assessed chemical and microbiological contamination in freshly ground red chili and turmeric sourced from traditional markets in Yogyakarta City. The investigation focused on microbiological contaminants, including Salmonella sp., Escherichia coli (E. coli), and yeast-and-mold counts, as well as chemical contaminants such as Rhodamine B, Methanyl Yellow, and formaldehyde. The findings revealed that Salmonella sp. were absent in all samples; however, each sample exceeded the permissible limits for E. coli and yeast-and-mold counts established by the Indonesian National Standard (SNI) 7388 : 2009. No chemical contaminants (Rhodamine B, Methanyl yellow, or formaldehyde) were detected in any sample. Therefore, although all ground spice samples were free from hazardous chemicals, they failed to meet essential microbiological hygiene standards, highlighting significant risks associated with their consumption.